Barriers to access of medical Cannabis as a healthcare option for service-connected disabled veterans - Landess, Mark W. (Kansas State University, 2022)
With the discovery of the endocannabinoid system in 1992, a medical and political debate has continued to spread across North America, both in the United States and Canada, for the last 20 years. Currently in the United States, there are 37 states and the District of Columbia that legalize the use of medical Cannabis (MC) by residents of those states diagnosed with a state-approved medical condition. Since MC is not recognized federally, millions of veterans suffering from service-connected disabilities are not eligible to utilize MC as a medical option. The U. S. Department of Veterans Affairs (VA) follows federal laws, which are not in line with current state laws, and service-connected disabled veterans suffer because they are denied access to a medication that has been shown to help alleviate many of the symptoms associated with the top ten service-connected disabilities. These conflicting laws can create stressful situations, which can affect the veteran and their family’s quality of life by limiting the veteran to use traditional medications (TM) commonly prescribed by the VA healthcare provider. This study utilized qualitative research methods, in order to explore lived experiences of service-connected disabled veterans (SCDV’s) and their families, where the SCDV utilized MC instead of TM to treat one or more service-connected disability (SCD). The sample consisted of four participating dyads, three were married with the other being in a long-term relationship, all of the participants were White, representing pre-9/11 and post-9/11 SCDV’s, who served in either the U.S. Army or U.S. Navy. After the raw data were analyzed, this study uncovered multiple findings that affected these families, including the different factors that led to the SCDV’s begin use of MC, stigmas related to medications used by the SCDV, the effects that MC had on these families, the impact that healthcare had on these families, as well as the future hope that these families had. All of these findings were affected by the use of MC by the SCDV.
Keywords: Barriers to healthcare; Service-connected disabled veterans; Service-connected disability; Medical cannabis; Traditional medications